Refresh your home : simple projects and tips to save money, update, and renovate (Reader's Digest, 2011)
Need to revive old trim, or fix wobbly outlets? Instead of hiring expensive contractors and landscapers, this guide will take you step by step through a wide range of do-it-yourself ideas for your home, garage, and yard.